Simple Noninvasive Scores Are Clinically Useful to Exclude, Not Predict, Advanced Fibrosis: A Study in Turkish Patients with Biopsy-Proven Nonalcoholic Fatty Liver Disease - YILMAZ, YUSUF (EDITORIAL OFFICE GUT & LIVER, 2020)
Background/Aims: Advanced fibrosis (F >= 3) indicates poor outcomes in nonalcoholic fatty liver disease (NAFLD). Here, we examined the diagnostic performance of the fibrosis-4 index (FIB-4) and NAFLD fibrosis score (NFS) for detecting (or excluding) advanced fibrosis in patients with biopsy-proven NAFLD. Methods The diagnostic performance of each non-invasive test according to previously identified cutoff points indicating low and high risk for advanced fibrosis was determined in 463 patients with NAFLD. Patients who scored <1.3 and >2.67 on the FIB-4 were considered at low and high risk for advanced fibrosis, respectively. Patients who scored <-1.455 and >0.676 on the NFS were considered at low and high risk for advanced fibrosis, respectively. Results: Eighty-one patients (17.5%) had biopsy-proven advanced fibrosis (F >= 3). The published FIB-4 cutoff values for low and high risk were able to exclude advanced fibrosis with negative predictive values (NPVs) of 0.907 and 0.843 and specificities of 74% and 97%, respectively. The published NFS cutoff values for low and high risk were able to exclude advanced fibrosis with NPVs of 0.913 and 0.842 and specificities of 63% and 96%, respectively. If biopsies were performed in only patients with a FIB-4 above the low cutoff point (>= 1.3), 67.1% could be avoided. Conversely, if biopsies were performed in only patients with an NFS above the low cutoff point (>=-1.455), 57.0% could be avoided. Conclusions: The main clinical utility of the FIB-4 and NFS in patients with NAFLD lies in the ability to exclude, not identify, advanced fibrosis.
Keywords: Non-alcoholic fatty liver disease; Liver fibrosis; Diagnostic test; Sensitivity and specificity; SCORING SYSTEMS; DIAGNOSIS; NAFLD